Mejoramiento y Ampliación del Sistema de Agua Potable del Centro Poblado Monte Alegre Irazola - Padre ABAD - Ucayali - Souza Del Aguila, Julio Augusto (2011)
The present formless of exhibition to opt the professional title for qualified professional experience, takes like exhibition topic and development of the technical file of the project: "IMPROVEMENT AND AMPLIFICATION OF THE SYSTEM OF it DILUTES DRINKABLE AND SEWER SYSTEM OF THE POPULATED CENTER MOUNTS CHEERFUL, DISTRITO DE IRAZOLA - COUNTY OF PADRE ABAD - REGIÓN UCAYALI", the part corresponding to the System of Drinkable Water, which was designated to the graduate one during the elaboration of the technical file. The Technical File of the Project that is described next, will be good to enlarge and to improve the System of Supply of Drinkable Water for the residents of the populated center it Mounts Cheerful - II stage, of the District of Irazola, County of Padre Abad and Department of Ucayali, corresponding its reach to the current and future population, in a horizon of twenty (20) years. The construction of the new service with the present project, will allow tohave appropriate infrastructure to supply with water of good quality, insure and continuous form, the illnesses of origin hydraulic and that that are presented by the environmental contamination diminishing this way. At the present time the MUNICIPALITY DISTRITAL DE IRAZOLA, is responsible for the administration of the system the supply of drinkable water in the stage of the populated center it Mounts Cheerful.